2020
DOI: 10.1167/iovs.61.11.19
|View full text |Cite|
|
Sign up to set email alerts
|

S100A4 Silencing Facilitates Corneal Wound Healing After Alkali Burns by Promoting Autophagy via Blocking the PI3K/Akt/mTOR Signaling Pathway

Abstract: Purpose This study investigated the role of S100 calcium binding protein A4 (S100A4) in corneal wound healing and the underlying mechanism of the S100A4-mediated PI3K/Akt/mammalian target of rapamycin (mTOR) pathway. Methods The rabbit corneal alkali burn model was established in vivo. S100A4 expression, wound healing, inflammation, and autophagy in rabbit cornea after alkali burn were detected. The NaOH-treated rabbit corneal stromal cells (rCSCs) were transfected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…1; for all online suppl. material, see www.karger.com/doi/10.1159/000516669) revealed various genes being strongly expressed in corneal tissue, including genes that are known to be relevant in corneal cell signaling, such as S100A6 and S100A4 [25], KERA , coding for keratocan, a protein essential for maintaining corneal shape and transparency [26], TGFBI , mutations of which are involved in various corneal dystrophies [27], and ANGPTL7 , which maintains corneal avascularity [28]. Profiles of different adaptive and innate immune cell types were identified in the transcriptional profile of 3 healthy corneas using the xCell deconvolution tool.…”
Section: Resultsmentioning
confidence: 99%
“…1; for all online suppl. material, see www.karger.com/doi/10.1159/000516669) revealed various genes being strongly expressed in corneal tissue, including genes that are known to be relevant in corneal cell signaling, such as S100A6 and S100A4 [25], KERA , coding for keratocan, a protein essential for maintaining corneal shape and transparency [26], TGFBI , mutations of which are involved in various corneal dystrophies [27], and ANGPTL7 , which maintains corneal avascularity [28]. Profiles of different adaptive and innate immune cell types were identified in the transcriptional profile of 3 healthy corneas using the xCell deconvolution tool.…”
Section: Resultsmentioning
confidence: 99%
“…The p70S6K is a downstream target of mTOR signaling and the mTOR is a serine/threonine protein kinase that has been found to affect many cellular functions, including cell growth, proliferation, and metabolism [58]. In addition, in a recent study of a rabbit alkali burn model, it was shown that the inhibition of the mTOR pathway promoted the autophagy and inhibited the proliferation, invasion, and migration of corneal stromal cells, promoting corneal wound healing [59]. Furthermore, it has been shown that mTOR signaling may induce scarring, neovascularization, and inflammation in the cornea [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining results of CD34 were associated with angiogenesis [ 27 ] and S100A4 was relevant to fibroblast cell migration and scar formation [ 28 ] ( Figure 6 A,B). Compared with the interior of MFUS tissue‐engineered skin (CS+GEL scaffolds, MFUS, and wound edge) and normal wound: 1.…”
Section: Resultsmentioning
confidence: 99%